Dios tan lejos y tan cerca: Itinerario místico-espiritual de Edith Stein - García Rojo, Jesús (Revista de espiritualidad, 2024)
A tireless seeker of truth, Edith Stein will not give up her efforts throughout her life. Until she reaches the goal, various stages will mark the journey, in which Teresa of Jesus and John of the Cross will be fundamental references. With the guidance of the Spanish mystics, Edith embraces Catholicism and enters Carmel, making God the center of her life. However, the more centered on God she is, the more aware she becomes of what is happening around her. According to her, praying for those in the world outside her religious community is a holy service, and the surrender of one’s will is the condition for mystical union.